Pendidikan Karakter Religius Siswa Dalam Perspektif Surah Al-Furqon Ayat 63-76 di SMK Muhammadiyah 1 Malang - Fathoni, Muhammad Sultan; Tobroni, Tobroni; Kamaludin, Mohammad (PAKAR Pendidikan, 2025)
Education is an effort to enhance positive values in various aspects, including academic and non-academic dimensions. Among the non-academic aspects that are essential to address is the inculcation of religious character values and their application in daily life. This research aims to examine the implementation of character values at SMK Muhammadiyah 1 Malang and to what extent the religious character values of its students align with the perspective of Surah Al-Furqan 63-76. The objective of this study is to deeply identify the process of instilling character values and analyze the religious character values of students at SMK Muhammadiyah 1 Malang from the perspective of Surah Al-Furqan 63-76. This study employs a qualitative method with a descriptive analysis approach. Data were collected through interviews, observations, and documentation. For data analysis, the researcher applied several steps: data collection, data reduction, data presentation, and conclusion drawing. The results of this study indicate that the inculcation of religious character values at SMK Muhammadiyah 1 Malang is carried out through various activities, such as welcoming students at school, performing congregational Dhuha prayers, reciting prayers before lessons, performing congregational Dzuhur prayers, and collectively reading the Quran. Students who have implemented the character values as outlined in Surah Al-Furqan 63-76 are generally satisfactory. However, most students have yet to apply certain values, such as performing night prayers and avoiding false testimony. Thus, SMK Muhammadiyah 1 Malang is expected to serve as a model for other vocational schools in developing and instilling religious character values.